Perturbation of nuclear–cytosolic shuttling of Rx1 compromises extreme resistance and translational arrest of potato virus X transcripts. (23rd March 2021) - Richard, Manon M. S.; Knip, Marijn; Schachtschabel, Joëlle; Beijaert, Machiel S.; Takken, Frank L. W.
Summary: Many plant intracellular immune receptors mount a hypersensitive response (HR) upon pathogen perception. The concomitant localized cell death is proposed to trap pathogens, such as viruses, inside infected cells, thereby preventing their spread. Notably, extreme resistance (ER) conferred by the potato immune receptor Rx1 to potato virus X (PVX) does not involve the death of infected cells. It is unknown what defines ER and how it differs from HR‐based resistance. Interestingly, Rx1 can trigger an HR, but only upon artificial (over)expression of PVX or its avirulence coat protein (CP). Rx1 has a nucleocytoplasmic distribution and both pools are required for HR upon transient expression of a PVX‐GFP amplicon. It is unknown whether mislocalized Rx1 variants can induce ER upon natural PVX infection. Here, we generated transgenic Nicotiana benthamiana producing nuclear‐ or cytosol‐restricted Rx1 variants. We found that these variants can still mount an HR. However, nuclear‐ or cytosol‐restricted Rx1 variants can no longer trigger ER or restricts viral infection. Interestingly, unlike the mislocalized Rx1 variants, wild‐type Rx1 was found to compromise CP protein accumulation. We show that the lack of CP accumulation does not result from its degradation but is likely to be linked with translational arrest of its mRNA. Together, our findings suggest that translational arrest of viral genes is a major component of ER and, unlike the HR, is required for resistance to PVX. Significance Statement: It is unknown how antiviral immunity is conferred in the case of extreme resistance. We show that extreme resistance correlates with a translational arrest of viral transcripts and can be uncoupled from the hypersensitive response, which was observed to not be required for viral immunity.